Elastic and ultrasonic properties of fermium monopnictides - Bala, Jyoti; Singh, Devraj (Engineering and Applied Science Research, 2020)
Determinations of higher order elastic constants, thermal properties, mechanical properties and ultrasonic behavior have been done for fermium monopnictides. Initially, the lattice and non-linearity parameters were used to compute the higher order elastic constants at temperatures of 0K, 100K, 200K and 300K by means of the Born potential mode. Variation of Cauchy’s relations has been found at higher temperature due to weak atomic interactions. The second order elastic constants (SOECs) were used to estimate mechanical parameters such as the Young’s modulus, bulk modulus, Pugh’s ratio, shear modulus, Zener’s anisotropy factor, hardness, and Poisson ratio. On the basis of the values of these parameters, we found a brittle nature of fermium monopnictides. Furthermore, the SOECs were applied to compute the wave velocities for shear and longitudinal modes of propagation along <100>, <110> and <111> crystallographic orientations. Properties such as the lattice thermal conductivity, acoustic coupling constant, thermal relaxation time and attenuation of ultrasonic waves due to thermo-elastic and phonon-phonon interaction mechanisms have been calculated at room temperature. The results of present investigation have been analysed with available findings on other rare-earth materials.